Recent Techno-Economic Potential and Development of Solar Energy Sector in India. Issue 3 (3rd May 2020) - Digambar Singh, A.; Yog Raj Sood, B.; Deepak, C.
ABSTRACT: Solar energy is an abundantly available free eco-friendly renewable energy source (RES). Solar energy holds great potential for providing a solution to the long-standing energy issues continuously faced by developing countries like India. The gap between power generation and demand is widening at an alarming rate in developing countries, especially in India. This gap can be filled by expansion of solar energy generation which has adequate potential to provide electricity. The current trends towards technical and economical potential of solar energy in India considering availability, current scenario, promotion scheme, recent investment, and strategies adopted for solar power generation has been presented in this paper. A detailed description of policies put forward by the Indian government in various states to encourage solar generation has been presented. In addition, the major achievements and future potential of RESs have also been described.